Genetic relatedness of Candida strains isolated from women with vaginal candidiasis in Malaysia - Chong, Pei Pei; Lee, Yee Lean; Tan, Boon Chong; Ng, Kee Peng (Microbiology Society, 2003)
The aims of this study were to compare the genetic relatedness of: (i) sequential and single isolates of Candida strains from women with recurrent vaginal candidiasis (RVC); and (ii) Candida strains from women who had only one episode of infection within a 1 -year period. In total, 87 isolates from 71 patients were cultured, speciated and genotyped by random amplification of polymorphic DNA (RAPD) analysis. Patients were categorized into three groups, namely those with: (i) a history of RVC from whom two or more yeast isolates were obtained (group A); (ii) a history of RVC from whom only a single isolate was obtained (group B); and (iii) a single episode of vaginal candidiasis within a 1 -year period (group C). Six yeast species were detected: Candida albicans, Candida glabrata, Candida lusitaniae, Candida famata, Candida krusei and Candida parapsilosis. Interestingly, the prevalence of non-albicans species was higher in group A patients (50%) than in patients in groups B (36%) or C (18.9%). Eighty RAPD profiles were observed, with a total of 61 polymorphic PCR fragments of distinct sizes. Clustering analysis showed that, overall, the majority of patients in group A had recurrent infections caused by highly similar, but not identical, sequential strains [mean pairwise similarity coefficient (SAB) = 0.721 ± 0.308]. The range of mean S AB values for intergroup comparisons for C. albicans isolates alone was 0.50-0.56, suggesting that there was no significant relatedness between strains from different groups. Genetic similarity of C. albicans isolates from patients in group A was lower than that of C. albicans isolates from patients in group C (mean SAB = 0.532 ± 0.249 and 0.636 ± 0.206, respectively); this difference was statistically significant (P = 0.036). These results demonstrate that the cause of recurrent infections varies among individuals and ranges between strain maintenance, strain microevolution and strain replacement; the major scenario is strain maintenance with microevolution. They also show that C. albicans strains that cause recurrent infections are less similar to each other than strains that cause one-off infections, suggesting that the former may represent more virulent subtypes.